Simultaneous attack strategy against a maneuvering target with unknown acceleration. (January 2019) - Hu, Zilun; Yang, Jianying
This paper is concerning the simultaneous attack problem with multiple missiles against a maneuvering target with unknown acceleration. The new guidance protocol, which avoids using the time-to-go information, ensures the simultaneous attack based on the consensus of the range-to-go and the approaching rate of each missile. This strategy is a distributed guidance law where each missile can only get information from neighbors. The consensus of the missiles is shown mathematically as well as with extensive simulations.